The Effect of Thematic Curriculum and Multimedia Use on Learning Interest and Critical Thinking Skills of High School Students in Central Java - Rahmania Sadek; Muhammad Al Muhajir; Irwan Irwan; Chandra Halim.M (West Science Social and Humanities Studies, 2024)
This study examines the effect of thematic curriculum and multimedia use on the learning interest and critical thinking skills of high school students in Central Java. A quantitative analysis was conducted using a sample of 160 students, with data collected through a Likert scale questionnaire. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that all hypothesized relationships are positive and significant. Specifically, multimedia use positively impacts both critical thinking skills and learning interest, while the thematic curriculum also positively influences critical thinking skills and learning interest. These findings suggest that integrating a thematic curriculum and multimedia tools can effectively enhance students' engagement and critical thinking abilities. The implications for educational practices and future research are discussed.